Benefits of a Pediatric Clinic Simulation Using Standardized Patients in Family Nurse Practitioner Education. Issue 6 (November 2021) - Weston, Cindy; Jones-Schubart, Kara; Hare, Martha; Gosselin, Kevin; Cook, Sharon
Abstract : Abstract: The purpose of this study was to examine the effect of a pediatric clinic simulation with standardized patients on anxiety, self-efficacy, and performance in family nurse practitioner students. A pediatric clinic simulation was developed in which family nurse practitioner students encountered standardized patients presenting for a well-child visit or exhibiting a common chief complaint. Anxiety and self-efficacy were assessed pre/post the simulation intervention, along with faculty-observed student performance. The clinic simulation resulted in increased self-efficacy, lower anxiety, and improved performance ( p < .01). High-fidelity simulation of a pediatric clinic was found to foster development of clinical competency, lower student anxiety, and improve self-efficacy. Abstract : Supplemental digital content is available in the text.